Aplikasi Pengaduan Masyarakat Pada SPKT Polres Semarang Menggunakan Sequential Search - achmad, haidhar; Rara Sriartati Redjeki (Elkom: Jurnal Elektronika dan Komputer, 2023)
The Semarang Police in the SPKT (Integrated Police Service Center) field has functions which include serving complaints from people affected by criminal acts, namely reports of fraud, robbery, embezzlement, theft, loss of valuables and so on. The high number of public complaints at this time so that people really need fast service in the SPKT section. SPKT is the spearhead of police services in providing services to the community to improve and facilitate services, an online complaint application is needed. This research is only used for reporting public complaints about traffic, crime and drugs that occur in Semarang district at the Integrated Police Service Center (SPKT) Semarang Police. The search method is only used to find the complaint number using the sequential search method. The results of the study show that the application of public complaints in the Semarang Police SPKT section makes it easier for the public to submit complaints to the Semarang Police regarding traffic, crime, drugs and searching for complaint numbers using the sequential search method